2016
DOI: 10.1017/s1751731115002141
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bovine ABCG2 polymorphism Y581S SNP on secretion into milk of enterolactone, riboflavin and uric acid

Abstract: The ATP-binding cassette transporter G2/breast cancer resistance protein (ABCG2/BCRP) is an efflux protein involved in the bioavailability and milk secretion of endogenous and exogenous compounds, actively affecting milk composition. A limited number of physiological substrates have been identified. However, no studies have reported the specific effect of this polymorphism on the secretion into milk of compounds implicated in milk quality such as vitamins or endogenous compounds. The bovine ABCG2 Y581S polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 36 publications
4
17
0
Order By: Relevance
“…ABCG2 plays an important role in uric acid transfer into milk, since its secretion was increased in dairy cow carriers of the Y581S polymorphism [150]. As suggested by the authors, the presence of this compound could affect the redox potential of milk.…”
Section: Polymorphisms In Transporters With Increased Expression Imentioning
confidence: 99%
“…ABCG2 plays an important role in uric acid transfer into milk, since its secretion was increased in dairy cow carriers of the Y581S polymorphism [150]. As suggested by the authors, the presence of this compound could affect the redox potential of milk.…”
Section: Polymorphisms In Transporters With Increased Expression Imentioning
confidence: 99%
“…It was further demonstrated that the milk-to-plasma ratio of EL decreased significantly in the Abcg2 (−/−) knockout female mice phenotype compared with the wild-type group (0.4 vs. 6.4) [62]. A subsequent study showed that EL was used as substrate to the bovine ABCG2 variant Y in vitro and was also actively secreted in milk resulting in a 2-fold increase in its milk-to-plasma ratio in Y/S heterozygous versus Y/Y homozygous cows [66]. The bovine ABCG2 Y581S variant has been described as a gain-of-function polymorphism that increases milk secretion and decreases plasma levels of its substrates [67,68,69].…”
Section: Effects Of Flaxseed Products On Milk El Concentrationmentioning
confidence: 99%
“…Edited sites were also observed in STAT5A and STAT5B, comprising transcription factors with critical roles in mammary differentiation and lactation (Liu et al, 1995;Cui et al, 2004). A number of other edited genes are important mediators of milk fat synthesis (LPL, ACACA, GPAM (Bionaz and Loor, 2008)) and secretion (XDH, PLIN3 (Bionaz and Loor, 2008)), or are involved in the transport of small molecules in milk: SLC37A1 (Pan et al, 2011), ABCG2 (Otero et al, 2016). Together, these genes represent some of the most prominent and well-published genes in lactation biology, and include many of the largest effect loci implicated in genetic regulation of these traits (He et al, 2011;Khatib et al, 2008;Bionaz and Loor, 2008;Kemper et al, 2016;Olsen et al, 2007).…”
Section: Rna Edited Genes and Qtlmentioning
confidence: 99%